Desain Dan Analisa Pembebanan Statik Terhadap Kekuatan Pelek Modifikasi Tipe Cast Wheel Pada Sepeda Motor Menggunakan Software Solidworks - Muslimin, Muslimin; Gunawan, Yuspian; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
In the automotive world, there have been many accidents caused by plasticdeformed rims. The purpose of this study was to design and analyze static loading on the modified rim strength of the cast wheel type on a motorcycle. The analytical method used to analyze is by using Solidworks software, analysis of static loading simulation to be carried out with 3 variations of the rim model and 3 variations in the number of spokes (8, 6, and 4 spoke) at a speed of 70 km/hr. From the results of the simulation analysis, all modification of the cast wheel rim type was analyzed, obtained the value of the safety factor included in the safe to use category. Modified rim type cast wheel model A with the number of spoke 8 obtained the largest maximum voltage value that is equal to 1,372,E+09 N/mm2, while for the smallest maximum voltage value obtained on rim model C with the number of spoke 4 which is 7,863,E+08 N/mm2 .Keywords: Static Loading, rim modification, cast wheel, solidworks software